Hubungan Karakteristik Petani Dengan Wellbeing Petani Padi di Desa Pelabuhan Dalam Kecamatan Pemulutan Kabupaten Ogan Ilir - M. Yamin; Nukmal Hakim; Nurilla Elysa Putri; Atikah Juliyanti Putri (Seminar Nasional Lahan Suboptimal, 2018)
Yamin et al, 2019. The Correlations of Farmer Characteristics With Wellbeing of Paddy Farmers in Pelabuhan Dalam Village Pemulutan Subdistrict Ogan Ilir Regency. pp. 270-280.The wellbeing measurement not only based on qualitative, but also leads to a condition of subjective wellbeing. The different of farmer characteristics will make the different result of objective wellbeing and subjective wellbeing The purposes of this research were to : (1) measure the objective wellbeing of paddy farmers in Pelabuhan Dalam Village Pemulutan Subdistrict Ogan Ilir Regency, (2) measure of subjective wellbeing of paddy farmers in Pelabuhan Dalam Village Pemulutan Subdistrict Ogan Ilir Regency, (3) analyze the correlation between the characteristics of paddy farmers with subjective wellbeing of Paddy Farmers in Pelabuhan Dalam Village Pemulutan Subdistrict Ogan Ilir Regency. This research was conducted in Pelabuhan Dalam Village Pemulutan Subdistrict Ogan Ilir Regency on May 2018. The research method used was survey method, with the sampling method was simple random sampling and took 30 sample. The results showed there were 18 farmers or 60 percent above poverty line and 12 farmers or 40 percent below poverty line. The subjective wellbeing of Paddy Farmers in Pelabuhan Dalam Village Pemulutan Subdistrict Ogan Ilir was included in the high category with an average score of 99,37 (score range 93,35 < x ≤120,00). Based on the calculation of rank Spearman correalation obtained there is no correlation between age and number of family members with subjective wellbeing, and there were correlation between formal education and total income with subjective wellbeing.